2018
DOI: 10.1186/s12968-018-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic arteriosclerosis is associated with left ventricular remodeling but not atherosclerosis: a TASCFORCE study

Abstract: BackgroundArteriosclerosis (arterial stiffening) is associated with future cardiovascular events, with this effect postulated to be due to its effect on cardiac afterload, atherosclerosis (plaque formation) progression or both, but with limited evidence examining these early in disease formation. The aim of the current study is to examine the association between arteriosclerosis, atherosclerosis and ventricular remodelling in a population at low-intermediate cardiovascular risk.MethodsOne thousand six hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Arteriosclerosis is associated with future cardiovascular events. In this study, Weir-McCall and colleagues [66] reported on 1651 subjects free of clinical cardiovascular disease with 10 year- cardiovascular disease risk score of < 20%. Whole body CMR angiography demonstrated impaired total arterial compliance correlated with LV mass to volume ratio in both men and women.…”
Section: Population Screeningmentioning
confidence: 99%
“…Arteriosclerosis is associated with future cardiovascular events. In this study, Weir-McCall and colleagues [66] reported on 1651 subjects free of clinical cardiovascular disease with 10 year- cardiovascular disease risk score of < 20%. Whole body CMR angiography demonstrated impaired total arterial compliance correlated with LV mass to volume ratio in both men and women.…”
Section: Population Screeningmentioning
confidence: 99%
“…1 Degenerative stiffness of the arterial beds is labeled as arteriosclerosis and should be differentiated from atherosclerosis, which is the result of endovascular inflammatory disease, lipid oxidation, and plaque formation. 2 Both usually coexist and represent a progressive, diffuse, and age-related process that occurs in all arterial beds. 3…”
Section: Introductionmentioning
confidence: 99%